Role of methionyl-transfer ribonucleic acid in the regulation of methionyl-transfer ribonucleic acid synthetase of Escherichia coli K-12. - Cassio, D (J Bacteriol, 1975)
A decrease in the in vivo acylation level of methionine transfer ribonucleic acid (tRNAmet) induced by methioninyl adenylate led to a specific derepression of methionyl-transfer ribonucleic acid (tRNA) synthetase formation. This derepression required de novo protein synthesis and was reflected by overproduction of unaltered enzyme. Two different strains of Escherichia coli K-12 that have normal levels of methionyl-tRNA synthetase were examined and the derepression of methionyl-tRNA synthetase was observed in both. Moreover, for one of these strains, the relation between the level of methionyl-tRNA synthetase and deacylation level of tRNAmet was established; under the growth conditions used, when more than 25% of tRNAmet was deacylated, methionyl-tRNA synthetase formation was derepressed and the level of derepression became proportional to the amount of tRNAmet deacylated. Concomitantly, the enzyme was subject to specific inactivation as a consequence of which the true de novo rate of derepression of the formation of this enzyme was higher than that determined by measurements of enzyme activity. These studies were extended to strains AB311 and ed2, which had a constitutive enhanced level of methionyl-tRNA synthetase. In these strains no derepression of enzyme formation was observed on reducing the acylation level of tRNAmet by use of methioninyl adenylate.